2011
DOI: 10.4067/s0034-98872011001200008
|View full text |Cite
|
Sign up to set email alerts
|

Meningomielitis asociadas a infección por herpes virus humano 7: Comunicación de dos casos

Abstract: Meningomyelitis associated with infection by human herpes virus 7. Report of two cases (Rev Med Chile 2011; 139: 1588-1591.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…One recent retrospective study over a 4-year period, showed that among 251 immunocompetent adults with neurological symptoms, a total of six cases were related to HHV-7: four meningitis cases, one myelitis case and one encephalitis case [ 17 ]. Another two cases of meningoencephalitis due to HHV-7 were reported in Chile [ 18 ], two cases of encephalitis [ 5 ] in Italy with one of them involving the nucleus of the VI cranial nerve [ 19 ] and one case of limbic encephalitis in Japan [ 8 ]. Generally, the diagnosis was made by PCRs on body fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent retrospective study over a 4-year period, showed that among 251 immunocompetent adults with neurological symptoms, a total of six cases were related to HHV-7: four meningitis cases, one myelitis case and one encephalitis case [ 17 ]. Another two cases of meningoencephalitis due to HHV-7 were reported in Chile [ 18 ], two cases of encephalitis [ 5 ] in Italy with one of them involving the nucleus of the VI cranial nerve [ 19 ] and one case of limbic encephalitis in Japan [ 8 ]. Generally, the diagnosis was made by PCRs on body fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Such method detects the nucleic acid in CSF particularly when obtained during the first week of symptoms onset, with a specificity of 99% and a sensitivity of 96%, while these percentages drop significantly after the second week [ 20 ]. Taking into consideration that HHV-7 was detected in normal brains [ 18 ], some studies support the fact that HHV-7 was detected in pia mater meninges, frontal lobe, temporal lobe and olfactory tract of individuals with encephalopathy [ 21 ] and controversial studies are still debating the role of HHV-7 in the pathogenesis of the Alzheimer disease [ 22 ]. More research is required to understand the role of HHV-7 in determining prognosis in immunocompetent adults.…”
Section: Discussionmentioning
confidence: 99%
“…One study also linked the presence of HHV-7 DNA and antigens in the brain to inflammatory-mediated hippocampal sclerosis and drug-resistant epilepsy ( 166 ). Other neurological disorders such as encephalitis, meningitis, myelitis, cerebellitis, neuritis, and meningo- or myeloradiculopathy (e.g., Guillian Barré syndrome) have also been observed during ongoing HHV-7 infection ( 6 , 128 , 129 , 139 141 , 143 158 , 160 165 , 167 , 168 , 170 ). In most cases, CNS manifestations ranging from nausea, sensitivity to light, and a stiff neck to ataxia and paralysis were accompanied by the detection of HHV-7 nucleic acids in cerebrospinal fluid (CSF) and/or synthesis of intrathecal anti-HHV-7 antibodies ( 6 , 129 , 140 , 141 , 143 158 , 160 164 , 167 , 168 ).…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Other neurological disorders such as encephalitis, meningitis, myelitis, cerebellitis, neuritis, and meningo- or myeloradiculopathy (e.g., Guillian Barré syndrome) have also been observed during ongoing HHV-7 infection ( 6 , 128 , 129 , 139 141 , 143 158 , 160 165 , 167 , 168 , 170 ). In most cases, CNS manifestations ranging from nausea, sensitivity to light, and a stiff neck to ataxia and paralysis were accompanied by the detection of HHV-7 nucleic acids in cerebrospinal fluid (CSF) and/or synthesis of intrathecal anti-HHV-7 antibodies ( 6 , 129 , 140 , 141 , 143 158 , 160 164 , 167 , 168 ). Of note, HHV-7-specific antibodies or DNA were usually not accompanied by the presence of other viral DNA or antibodies, ruling out potential leakage through the blood-brain barrier (BBB) and indicating that HHV-7 can invade the nervous system.…”
Section: Clinical Manifestationsmentioning
confidence: 99%